Translating proverbs between Malay and Arabic from a linguistic perspective to semantic change (Strategy and Pillars) - Mohd Azizul Rahman Bin Zabidin; Ummu Hani Binti Abbas (Departement of Arabic Language and Literature, IAIN Syekh Nurjati Cirebon, 2021)
It is noticeable that most non-Arabic students may face great difficulty when translating Arabic proverbs into Malay or vice versa due to their lack of familiarity with the Arab culture of wisdom and proverbs, as they have translated Arabic proverbs into Malay inspired by the cultural elements of the Malay language. From this standpoint, this research aims to study translation strategies and their foundations between Arabic and Malay proverbs. It also aims to identify the best strategies, and the most appropriate for translating Arabic proverbs for students of non-Arabic speakers, especially Malay Students. The research follows the descriptive and analytical approach because it is the most appropriate for the topic. The research reached many results, the most important of which are: It is unsuitable to apply the literal translation method in translating proverbs, as it may lead to the loss of the proverb meaning. The “equivalence method” is one of the best strategies in translating proverbs to convey the message and to understand its meanings for non-Arabic speaking students, avoiding corruption in the meaning to be conveyed, and preserving the method. This method would increase the desire of non-Arabic speaking students and encourage them to study Arab cultures through proverbs, in addition to keeping them away from the boredom resulting from the production of ambiguous translation that raises questions about the significance of the correct message.